Lymphocytes Tγδ in clinically normal skin and peripheral blood of patients with systemic lupus erythematosus and their correlation with disease activity - Ewa Robak; Hanna Niewiadomska; Tadeusz Robak; Jacek Bartkowiak; Jerzy Z. Blonski; Anna Wozniacka; Lech Pomorski; Anna Sysa-Jedrzejowska (Hindawi Limited, 2001)
Human Tγσ lymphocytes constitute from 1 to 15% of all peripheral blood lymphocytes. Recent work has demonstrated that this population plays a major role in the pathogenesis of infectious and immune diseases. Increased numbers of γσ T cells have been found in affected skin from systemic sclerosis and chronic cutaneous lupus erythematosus patients.